Process design and optimization of EDTA-biojarosite – a treatment approach in the Box–Behnken framework - Bhaskar S.; Manoj A.; Resmi S. R.; Divyashree S.; Sreenivasa M. Y. (Water Practice and Technology, 2023)
A study was conducted to investigate the performance of biojarosite as a catalyst in Fenton oxidation with and without the presence of the chelating agent ethylene diamine tetra acetic acid (EDTA). The addition of EDTA resulted in increased iron dissolution, confirming the role of EDTA as a chelating agent. The heterogeneous catalytic properties of jarosite were confirmed by the removal efficiencies of 93.5 and 83.4%, with and without EDTA, respectively. The Box–Behnken method was employed as a Design of Experiments tool to identify suitable experimental runs. Both Fenton oxidation and EDTA-based Fenton oxidation were examined separately, with PCP removal being the response variable. In the case of Fenton oxidation, the optimization process resulted in the selection of 0.1–1 g/L of iron catalyst, 100–1,000 mg/L of H2O2, and a pH range of 2.5–3.5. On the other hand, for EDTA-based Fenton oxidation, the optimal conditions were determined to be 0.1–1 g/L of iron catalyst, 100–1,000 mg/L of H2O2, and a pH range of 6.5–7.5. ANOVA was conducted to analyze the results, and the model fit was examined. HIGHLIGHTS Application of Box–Behnken design procedure for Fenton's oxidation of pentachlorophenol.; Use of biojarosite-based catalyst for Fenton's oxidation.; EDTA-based Fenton's oxidation at near neutral pH.; Comparison of the efficiency of the process with or without EDTA as a chelating agent.;